2011
DOI: 10.1107/s160053681103159x
|View full text |Cite
|
Sign up to set email alerts
|

Opipramolium fumarate

Abstract: In the crystal structure of the title salt {systematic name: 4-[3-(5H-dibenz[b,f]azepin-5-yl)prop­yl]-1-(2-hy­droxy­eth­yl)piperazin-1-ium (2Z)-3-carb­oxy­prop-2-enoate}, C23H30N3O+·C4H3O4 −, the piperazine group in the opipramol cation is protonated at only one of the N atoms. In the cation, the dihedral angle between the two benzene rings is 53.5 (6)°. An extensive array of inter­molecular O—H⋯O, O—H⋯N and N—H⋯O hydrogen bonds and weak inter­molecular N—H⋯O, C—H⋯O and C—H⋯π inter­actions dominate the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Our research group has published a number of papers on incorporated heterocyclic ring structures, viz. imatinibium dipicrate (Jasinski et al, 2010), 1-(2-hydroxyethyl)-4-[3-(2trifluoromethyl-9H-thioxanthen-9-ylidene)propyl]piperazine-1,4-diium dichloride, which is the dihydrochloride salt of flupentixol (Siddegowda et al, 2011a) and opipramolium fumarate (Siddegowda et al, 2011b). Other related crystal structures are 4-(pyrimidin-2-yl)piperazin-1-ium (E)-3-carboxyprop-2-enoate (Yamuna et al, 2014a), flupentixol tartarate and enrofloxacinium oxalate (Yamuna et al, 2014b,c).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Our research group has published a number of papers on incorporated heterocyclic ring structures, viz. imatinibium dipicrate (Jasinski et al, 2010), 1-(2-hydroxyethyl)-4-[3-(2trifluoromethyl-9H-thioxanthen-9-ylidene)propyl]piperazine-1,4-diium dichloride, which is the dihydrochloride salt of flupentixol (Siddegowda et al, 2011a) and opipramolium fumarate (Siddegowda et al, 2011b). Other related crystal structures are 4-(pyrimidin-2-yl)piperazin-1-ium (E)-3-carboxyprop-2-enoate (Yamuna et al, 2014a), flupentixol tartarate and enrofloxacinium oxalate (Yamuna et al, 2014b,c).…”
Section: Chemical Contextmentioning
confidence: 99%
“…For cinnarizine as a calcium channel blocker, see: Terland & Flatmark (1999), as a nootropic drug, see: Towse (1980) and for a clinical evaluation in various allergic disorders, see: Barrett & Zolov (1960). For related structures, see: Bertolasi et al (1980); Dayananda et al (2012); Jasinski et al (2011); Mouillé et al (1975); Siddegowda et al (2011); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…Cinnarizine can be used in scuba divers without an increased risk of central nervous system oxygen toxicity. The crystal structures of some related compounds viz., cinnarizine (Mouillé et al, 1975), cyclizine hydrochloride (Bertolasi et al, 1980), cinnarizinium dipicrate (Jasinski et al, 2011), cinnarizinium picrate (Song et al, 2012), opipramolium fumarate (Siddegowda et al, 2011) and cinnarizinium 3,5-dinitrosalicylate (Dayananda et al, 2012) have been reported. In continuation of our work on the salts of pharmaceutical compounds and in view of the importance of cinnarizine, this paper reports the crystal structure of the title salt, C 26 H 29 N 2 + .…”
Section: S1 Commentmentioning
confidence: 99%
“…For applications of opipramol, see: Moller et al (2001). For related structures, see: Jasinski et al (2010); Fun et al (2011); Siddegowda, Butcher et al (2011); Siddegowda, Jasinski et al (2011); Swamy et al (2007). For graph-set analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…However, it has pronounced D2-, 5-HT2-, and H1-blocking potential and high affinity to sigma receptors (sigma-1 and sigma-2). The crystal structures of opipramol dipicrate (Jasinski et al, 2010), opipramol (Fun et al, 2011), opipramolium fumarate (Siddegowda, Butcher et al, 2011) and flupentixol dihydrochloride (Siddegowda, Jasinski et al, 2011) have been reported recently. In view of the importance of the title compound we herein report its molecular and crystal structure.…”
Section: S1 Commentmentioning
confidence: 99%